Pelatihan Administrasi Perkantoran Bagi Mahasiswa Perbankan Syariah STEBIS IGM - Fadilla Fadilla; Doly Nofiansyah (AKM, 2021)
This community service activity is the provision of training on office administration as a provision before students undertake an internship. Participants in this office administration briefing activity are Semester 5 Sharia Banking students who cannot intern at bank and bank financial institutions due to covid 19. The purpose of this office administration training is so that students can understand how to work in an office, what activities can be done there. In this office administration training, the speakers provide knowledge about what administration is, the scope of administration in the office, what activities will be carried out in the office. In this provision, students will also be given training on how to combine files into one PDF format. Students will also be given knowledge about accreditation and preparation of evidence in accreditation criteria 9 forms.